Implementasi Kurikulum Merdeka Pada Satuan Pendidikan Perguruan Tinggi - Sulastini, Rita; Sakuroh, Lilis; Awaliyah, Wiwin; Dadang, Dadang (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The domain of higher education plays a crucial role in cultivating exceptional human resources. The primary emphasis of education reform in Indonesia is the implementation of the Independent Curriculum. This article examines the execution of the Merdeka Curriculum at higher education institutions to evaluate its influence on learning and the attainment of learning objectives. The objective of this study is to determine the most effective methods for implementing the Merdeka Curriculum in higher education, assess the opinions of both lecturers and students regarding the Merdeka Curriculum, and evaluate its influence on the attainment of learning objectives. This study employs a mixed strategy, integrating both qualitative and quantitative methodologies. The qualitative technique entails conducting comprehensive interviews with instructors and analyzing policy papers. Concurrently, the quantitative approach entails conducting surveys among students to gauge their impressions of the Merdeka Curriculum, as well as employing statistical analysis to assess the attainment of learning objectives. The research findings indicate that there are differences in the approaches used to apply the Independent Curriculum, which involve modifications to resources, teaching techniques, and evaluation systems. The lecturers and students had favorable reactions to this strategy, perceiving it as a pioneering measure in enhancing the curriculum's alignment with the demands of the job market. The data analysis indicates that students who participate in the Merdeka Curriculum exhibit a greater degree of pleasure and attain superior learning outcomes in comparison to the control group. In addition, it was mentioned that the introduction of the Independent Curriculum in higher education had a beneficial effect on learning and the attainment of learning objectives. By employing an appropriate methodology, a combination of qualitative and quantitative approaches offers a comprehensive comprehension of the execution of the Merdeka Curriculum and furnishes valuable direction for subsequent curriculum enhancement.Keywords: Independent Curriculum; Education units; CollegeAbstrak:Ranah pendidikan tinggi memegang peranan penting dalam menumbuhkan sumber daya manusia yang unggul. Penekanan utama reformasi pendidikan di Indonesia adalah penerapan Kurikulum Mandiri. Artikel ini mengkaji penerapan Kurikulum Merdeka di perguruan tinggi untuk mengevaluasi pengaruhnya terhadap pembelajaran dan pencapaian tujuan pembelajaran. Tujuan penelitian ini adalah untuk mengetahui metode penerapan Kurikulum Merdeka yang paling efektif di perguruan tinggi, menilai pendapat dosen dan mahasiswa mengenai Kurikulum Merdeka, dan mengevaluasi pengaruhnya terhadap pencapaian tujuan pembelajaran. Penelitian ini menggunakan strategi campuran, yang mengintegrasikan metodologi kualitatif dan kuantitatif. Teknik kualitatif mencakup melakukan wawancara komprehensif dengan instruktur dan menganalisis makalah kebijakan. Sementara itu, pendekatan kuantitatif mencakup pelaksanaan survei di kalangan siswa untuk mengukur kesan mereka terhadap Kurikulum Merdeka, serta menggunakan analisis statistik untuk menilai pencapaian tujuan pembelajaran. Temuan penelitian menunjukkan bahwa terdapat perbedaan pendekatan yang digunakan untuk menerapkan Kurikulum Mandiri, yang melibatkan modifikasi sumber daya, teknik pengajaran, dan sistem evaluasi. Para dosen dan mahasiswa mempunyai reaksi positif terhadap strategi ini, dan menganggapnya sebagai langkah perintis dalam meningkatkan keselarasan kurikulum dengan tuntutan pasar kerja. Analisis data menunjukkan bahwa siswa yang mengikuti Kurikulum Merdeka menunjukkan tingkat kesenangan yang lebih besar dan memperoleh hasil belajar yang lebih unggul dibandingkan dengan kelompok kontrol. Selain itu disebutkan bahwa pemberlakuan Kurikulum Mandiri pada perguruan tinggi memberikan pengaruh yang menguntungkan terhadap pembelajaran dan pencapaian tujuan pembelajaran. Dengan menggunakan metodologi yang tepat, kombinasi pendekatan kualitatif dan kuantitatif memberikan pemahaman komprehensif tentang pelaksanaan Kurikulum Merdeka dan memberikan arahan yang berharga untuk penyempurnaan kurikulum selanjutnya.Kata Kunci: Kurikulum Merdeka; Satuan Pendidikan; Perguruan Tinggi